A Review of the Space Trajectory Planning of Redundant Manipulator - Gao Han; Zhang Minglu; Zhang Xiaojun (Jixie chuandong)
The redundant manipulator can use redundant degree of freedom to avoid obstacles,but it does not affect the operation of the end effecter. So comparing with general non- redundant manipulator,the redundant manipulator has obvious advantages for dealing with obstacle avoidance. Recently,the space trajectory planning research of redundant manipulator has not yet formed a set of overall framework. It is necessary to analysis and in- depth summary the existing research results of system. The space trajectory planning of redundant manipulator basic theory and practical application are discussed. According to the different modeling principle,it is divided into five categories. The advantages and disadvantages of these methods are Summed up in detail and redundant manipulator trajectory planning conception and the future development trend are prospected.